Afroperuvian feminisms and performance geographies of diasporicity, 1953–2013. Issue 4 (19th December 2017) - Dorr, Kirstie A.
Abstract: This essay charts a vibrant geohistory of Black women's cultural activism in Lima, Perú from the mid‐twentieth century to the present. Specifically, it integrates the analytics and vocabularies of sound studies, critical race and gender studies, and feminist geography to examine convergences within the cross‐generational work of three Black women performers–U.S. artist Katherine Dunham and Afro‐Peruvian artists Victoria Santa Cruz and Susana Baca. I argue that despite differences in content and form, and at times in approach or aspiration, their collective work as political activists and cultural producers can be understood as both formed by and formative of performance geographies of feminist diasporicity., I offer a geo‐cultural reading of performed texts and pedagogical practices from each artist to examine how the mobilization of spatialized expressive practices such as siting and staging, and spatial imaginaries such as the "Black Pacific, " and the "Afro‐diasporic" to contest and reimagine the socio‐spatial relations that constitute the more intimate scales of the home and the domestic. I conclude that these respatializations of raced and gendered embodiment advance deprovincialized manifestations of the historical continuities, transnational ties, and internationalist impulses that connect otherwise localized and specific stories of diasporic cultural formation in the Black Americas.